1993
DOI: 10.1063/1.354015
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of elastic constants, refractive index, and lattice parameter of cubic zirconia at high temperatures

Abstract: Acoustic mode frequency, lattice parameter, and refractive index measurements have been carried out on single crystals of cubic stabilized zirconia, ZrO2(xY2O3), in the temperature range 300 to 1450 K, using Brillouin scattering, x-ray diffraction, and interferometric methods, respectively. Elastic constants Cij and associated quantities such as the bulk modulus B=(C11+2C12)/3, the anisotropy ratio A=2C44/(C11−C12), and the Cauchy relation failure Δ=(C12−C44) have been determined from these measurements. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…(15) not only in the range 2.5 < k < 7 lm but also for 7 < k < 9 lm. One should remember that the error of this approach may be considerable in the last range.…”
Section: Theoretical Modelling Of Radiative Properties Of Porous Ceramentioning
confidence: 95%
See 1 more Smart Citation
“…(15) not only in the range 2.5 < k < 7 lm but also for 7 < k < 9 lm. One should remember that the error of this approach may be considerable in the last range.…”
Section: Theoretical Modelling Of Radiative Properties Of Porous Ceramentioning
confidence: 95%
“…It was shown that index of refraction decreases monotonically with yttria stabilizer concentration in the range between 10.9 and 32.4 mol.% Y 2 O 3 . Some additional data for temperature dependence of refractive index for zirconia with 9.4 and 24 mol.% of yttria were given in paper [15]. The measurements at wavelength k = 0.51 lm showed an increase in refractive index of about 6% in the temperature range 300 < T < 1450 K.…”
Section: The Data From the Literaturementioning
confidence: 97%
“…Since only samples with trivalent dopant and co-dopant and substantial cphase (5ScYSZ and 5YbYSZ) exhibited the endothermic reaction, it is believed that this reaction may be associated with defect clustering/ordering during cooling. In fact, it has been observed in other research that the oxygen vacancies in c-phase preferentially locate on the next nearest neighbour to the substitutional dopant cations such as Y 3+ (Sc 3+ and Yb 3+ ) forming highly localized oxygen-cation clusters [28][29][30]. Upon reheating to a critical temperature, rapid diffusion of oxygen anions may occur producing a disordered structure [31].…”
Section: Dsc Analysis Of Phase Transformationmentioning
confidence: 91%
“…Calculation of the associated stress is made using elastic constants for an isotropic polycrystal of YSZ (Table 1). These constants are calculated from the elastic constants of the single crystal [8], using the Voigt model. The stress level obtained is in agreement with the literature [9] [10]: after manufacturing, the electrolyte is under strong bi-axial compressive stresses.…”
Section: Macroscopic X-ray Measurementsmentioning
confidence: 99%